Leadership Dalam Pendidikan - Almaydza Pratama Abnisa (STAI Asy-Syukriyyah, 2016)
Discussing leadership is essentially to discuss the intricacies of human society. Humans are social creatures, instinctively need to get along and needing another human in the process they form groups, communities, nations and state, which in turn needs a leader. A joint community leaders work together to organize, build, promote and defend the community. Leadership is understood as all efforts together to mobilize all the resources and tools available within an organization. Resources can be classified into two major parts, namely: human resources and non-human resources. In educational institutions, especially the educational institutions of Islam consists of various elements or sources, and humans are the most important element, so the success or failure of an organization to achieve its intended purpose is highly dependent on the ability of its leaders to foster a climate of cooperation easily and can mobilize resources existing power, so it can be run effectively and efficiently. Thus, the life of an organization is determined by the role of a leader. Effective leadership is the leadership that is able to grow and develop business cooperation and maintain a favorable climate in organizational life. Good leadership is leadership that can integrate with the task orientation of human relations orientation.